Recent Advances in Information and Communication Technology 2016 Proceedings of the 12th International Conference on Computing and Information Technology (IC2IT) - Meesad, Phayung; Boonkrong, Sirapat; Unger, Herwig; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This proceedings book presents recent research work and results in the area of communication and information technologies. The chapters of this book contain the main, well-selected and reviewed contributions of scientists who met at the 12thInternational Conference on Computing and Information Technology (IC2IT) held during 7th - 8th July 2016 in Khon Kaen, Thailand The book is divided into three parts: "User Centric Data Mining and Text Processing", "Data Mining Algoritms and their Applications" and "Optimization of Complex Networks".
Invited Paper -- User Centric Data Mining and Text Processing -- Data Mining Algorithms and Their Applications -- Optimisation of Complex Networks.
Keywords: Computational intelligence; Artificial intelligence; Computational Intelligence; Artificial Intelligence